Resource Assessment of Larimichthys crocea in the East China Sea Based on eDNA Analysis - Wu, Lisheng; Li, Jianlong; Tong, Feng; Zhang, Jiajun; Li, Miaomiao; Ding, Shaoxiong (Frontiers in Marine Science, 2022)
Environmental DNA (eDNA) is a promising tool for rapid and noninvasive biomonitoring and resource assessment. Broadly, two main PCR-based strategies of biodiversity monitoring can be deployed for eDNA analysis. The first one consists of targeting single species using standard PCR, real-time quantitative PCR (qPCR), or droplet digital PCR (ddPCR). The second strategy aims to simultaneously detect multiple species relying on High-Throughput Sequencing (i.e. eDNA metabarcoding). The aim of this study was to further explore a convenient and feasible method to correctly assess fishery resources using eDNA technology for large yellow croaker (Larimichthys crocea). Two eDNA methods (metabarcoding and qPCR) were used to investigate the biomass and distribution of large yellow croaker in the autumn and spring seasons in the central and southern regions of the East China Sea, and these results were compared with the results of a bottom trawling fishery survey. The results suggested that the designed NADH2-specific primers and developed real-time qPCR method were more applicable and reliable. The variation in the eDNA concentration of large yellow croakers coincided well with that of a real capture survey in the East China Sea. The difference in eDNA concentration between the surface and bottom water samples reflected the distribution characteristics in the water layer related to the life history of L. crocea in the two seasons. The developed methods based on eDNA technology and real-time qPCR could not only be used to evaluate the resource distribution but could also contribute to estimating the life history and migration route of large yellow croaker.